Factores asociados a las conductas hipercinéticas en la población infantojuvenil y su repercusión familiar y educacional. - Dos Santos Ramos, Jair José (Machala : Universidad Técnica de Machala, 2019)
Introduction: Hyperkinetic disorder is one of the most common neurobehavioral disorders in children, with a worldwide prevalence of approximately 3.4% to 7.2%; and a strong hereditary component in its etiology; however environmental factors and gene-environment interaction also play an important role in its etiology. Objective: To describe the factors associated with hyperkinetic disorder in the child and adolescent population, and their family and educational impact through review and analysis of bibliographic articles. Methodology: This work is done through systematic research in scientific search engines such as Pubmed, Cochrane, Google Scholar, ScienceDirect, then we selected articles of importance published in the last 5 years. Result: It is determined that the hyperkinetic disorder presents many etiologies, with greater relevance for the genetics factor and an important participation of the environment factor and the gene - environment interaction, with significant negative repercussions at the family and academic levels. Conclusion: In addition to the hereditary factor there is a greater susceptibility to present a diagnosis of hyperkinetic disorder the offspring of pregnant women who are exposed to tobacco, lead, pesticides OP (phosphorus organs), mercury, in addition to paracetamol for long period, who have ovarian syndrome polycystic, maternal stress, alcoholism, poor iodine diet and multivitamins; and premature children, very low birth weight, who consume excessively processed foods, a diet low in Omega - 3 polyunsaturated fatty acids, which live in conflictive family environments; they are prone to low academic performance, problematic interfamilial relationships, and in adulthood to professional and interpersonal problems.
Introducción: El trastorno hipercinético es uno de los trastornos neuroconductuales infantiles más comunes, con una prevalencia mundial de aproximadamente de 5% al 7%; y una fuerte componente hereditaria en su etiología; sin embargo los factores ambientales y la interacción gen-ambiente también juegan un papel importante en su etiología. Objetivo: Describir los factores asociados a las conductas hipercinéticas en la población infantojuvenil, y su repercusión familiar y educacional mediante revisión y análisis de artículos bibliográficos. Metodología: Este trabajo se realiza mediante una investigación sistemática en los buscadores científicos como Pubmed, Cochrane, Scholar Google, ScienceDirect, luego seleccionamos artículos de importancia publicados en los últimos 5 años. Resultado: Se determina que el trastorno de conducta hipercinética presenta vías causales múltiples, con mayor relevancia para el factor herencia y una importante participación del factor ambiente y de la interacción gen – ambiente, con repercusiones negativas significativas a nivel familiar y académica. Conclusión: Además del factor hereditario hay una mayor susceptibilidad de presentar un diagnóstico de trastorno hipercinético la descendencia de las mujeres embarazadas que se expongan al tabaco, plomo, pesticidas OP (órganosfosforados), mercurio, además del paracetamol por largo periodo, que presentan síndrome de ovario poliquístico, estrés materno, alcoholismo, dieta pobre en yodo y multivitaminas; y niños prematuros, muy bajo peso al nacer, que consumen comidas procesadas excesivamente, dieta pobre en ácidos grasos poliinsaturados Omega – 3, que viven en entornos familiares conflictivos; son propensos a un bajo rendimiento académico, relacionamientos interfamiliar problemáticas, y en la adultez a problemas profesionales e interpersonales.
Keywords: CONDUCTA HIPERCINETICO; FACTORES ASOCIADOS; REPERCUSION; FAMILIAR